O avanço tecnológico e a responsabilidade social das empresas na proteção de dados pessoais: uma abordagem sobre a adoção de medidas de compliance com a Lei Geral de Proteção de Dados Pessoais - Baccari, Jhesica Loures dos Santos (2021)
The Society is undergoing a digital transformation and accelerated transfer of data and personal information in electronic media; it is precisely this reason that leads to concerns about how companies should react to this scenario of personal data protection of citizens in Brazil. The search for power over personal data is old, and this work brings to light analyzes of cases such as Hitler and the scandal of the Cambridge Analytic company in the elections of President Donald Trump, which were used as an analogy to explain the consequences of the social damage caused. by the lack of procedures and good practices in the processing of personal data. It was necessary to carry out a survey of the legal frameworks on the subject since its first registration in 1710 with the Queen Anne Statute, and to understand the background of this Federal Law in Brazil, which has European roots; after the repeal of Directive 95, which focused on European Regulation 679 in 2016, all countries that make up the European Union had to create legislation on the protection of personal data - a requirement to maintain international relations between countries. It gained emphasis on human and fundamental rights due to the nature of privacy inherent to the human person, but in return, it generated the obligation of service providers, which in this work will deal only with companies, to comply with the new rules of the General Data Protection Law Personal - Law 13.709/2018. With this, it will be necessary to guide and report to companies about their responsibilities, publish a text that informs exactly what they must do at this time, to comply with social responsibility, transparency with the customer, employees, suppliers and partners, that is, the people with whom it maintains a commercial relationship to maintain the economic turnover, above all, built-in legal and technological security through compliance based on procedures